LANGKAH PROAKTIF MAHASISWA DALAM MEMBANGUN BUDAYA LITERASI MENUJU MASYARAKAT YANG LEBIH BERPENGETAHUAN - Yuni Sri Rezeki; Veronika Azarya Hotmaida; Ichsan Fauzi Rachman (Kampus Akademik Publiser, 2024)
This research aims to find out how students can be proactive in building literacy towards a knowledgeable society in the digital era. This research uses a literature study method with stages; literature study, data collection and analysis. This research discusses how literacy has become the main key to the success and development of society in today's rapidly developing digital era. As important agents of change, students have a significant role in forming a strong literacy culture and building a more knowledgeable society in the digital era. Changing policies through forums or student organizations is a proactive way to make changes in digital literacy education. Students can encourage the inclusion of digital literacy curricula at all levels of education and encourage additional resources to help students and the broader community understand digital issues. This can be achieved by developing proposals, meeting with universities or educational policy makers, and holding awareness campaigns. We can also work with libraries and other community organizations to organize digital literacy workshops, especially for underserved groups such as the elderly who do not have the necessary skills to utilize digital resources.